LIFE AND FERTILITY TABLES OF Pineus boerneri ANNAND (HEMIPTERA: ADELGIDAE) ON Pinus spp. (PINACEAE) - Cardoso, Josiane Teresinha; Lazzari, Sonia Maria Noemberg (Floresta, 2016)
Biological parameters of Pineus boerneri were evaluated in laboratory using seedlings of Pinus taeda and Pinus elliottii. The nymphs were observed along their development. The total life cycle was not significantly different on P. taeda and P. elliottii, being, respectively, 69 and 65 days. The same trend was observed for mean fecundity, being about 40 eggs/female on P. taeda and 53 on P. elliottii. However, when daily mean fecundity was considered, the difference was significant, being 1.3 eggs/female/day on P. taeda and 1.8 on P. elliottii. The nymphal mortality was greater on P. taeda (50%) than on P. elliottii (28%). These results reflected on life expectancy which was higher on P. elliottii for the nymphal stage, but for the adult stage there was no significant difference between both host plants. The intrinsic rate of natural increase and the finite rate of increase were similar, indicating that P. boerneri shows the same reproductive capacity on both hosts, despite the net reproductive rate being much greater on P. elliottii (23.8 eggs/female) than on P. taeda (15.4). The highest nymphal survival and reproductive rates on P. elliottii indicate that this host plant is more suitable for the development of P. boerneri.